Outcomes after surgery in patients with diabetes who used metformin: a retrospective cohort study based on a real-world database. Issue 2 (30th November 2020) - Lin, Chao-Shun; Chang, Chuen-Chau; Yeh, Chun-Chieh; Chang, Yi-Cheng; Chen, Ta-Liang; Liao, Chien-Chang
Abstract : Introduction: Limited information was available regarding the perioperative outcomes in patients with and without use of metformin. This study aims to evaluate the complications and mortality after major surgery in patients with diabetes who use metformin. Research design and methods: Using a real-world database of Taiwan's National Health Insurance from 2008 to 2013, we conducted a matched cohort study of 91 356 patients with diabetes aged >20 years who used metformin and later underwent major surgery. Using a propensity score-matching technique adjusted for sociodemographic characteristics, medical condition, surgery type, and anesthesia type, 91 356 controls who underwent surgery but did not use metformin were selected. Logistic regression was used to calculate the ORs with 95% CIs for postoperative complications and 30-day mortality associated with metformin use. Results: Patients who used metformin had a lower risk of postoperative septicemia (OR 0.94, 95% CI 0.90 to 0.98), acute renal failure (OR 0.87, 95% CI 0.79 to 0.96), and 30-day mortality (OR 0.79, 95% CI 0.71 to 0.88) compared with patients who did not use metformin, in both sexes and in every age group. Metformin users who underwent surgery also had a decreased risk of postoperative intensive care unit admission (OR 0.60, 95% CI 0.59 to 0.62) and lower medical expenditures (p<0.0001) than non-use controls. Conclusions: Among patients with diabetes, those who used metformin and underwent major surgery had a lower risk of complications and mortality compared with non-users. Further randomized clinical trials are needed to show direct evidence of how metformin improves perioperative outcomes.